![a)({2a + x} \: )^{2} = \\ b)( {3x + 2y})^{2} = \\ c)( {4ab + 2x)}^{2} = \\ d)( {x + y})^{2} = \\ e)( {ab + bc)}^{2 = } a)({2a + x} \: )^{2} = \\ b)( {3x + 2y})^{2} = \\ c)( {4ab + 2x)}^{2} = \\ d)( {x + y})^{2} = \\ e)( {ab + bc)}^{2 = }](https://tex.z-dn.net/?f=a%29%28%7B2a+%2B+x%7D+%5C%3A+%29%5E%7B2%7D++%3D++%5C%5C+b%29%28+%7B3x+%2B+2y%7D%29%5E%7B2%7D++%3D++%5C%5C+c%29%28+%7B4ab+%2B+2x%29%7D%5E%7B2%7D+%3D++%5C%5C+d%29%28+%7Bx+%2B+y%7D%29%5E%7B2%7D+%3D++%5C%5C+e%29%28+%7Bab+%2B+bc%29%7D%5E%7B2+%3D+%7D+)
Soluções para a tarefa
Respondido por
0
Resposta:
Explicação passo-a-passo:
a
( 2a + x)² =] (2a)² + 2 * 2a * x + (x)² ] =4a²+ 4ax + x² ***resposta
b
( 3x + 2y )² = [ (3x)² + 2 * 3x * 2y + (2y)² ] = 9x² + 12xy + 4y² ****resposta
c
( 4ab + 2x)² = [ (4ab)² + 2 * 4ab * 2x + (2x)² ] = 16a²b² + 16abx + 4x² *****resposta
d
( x + y)² = [ (x)² + 2 * x * y + (y)² ] = x²+ 2xy + y² ***** resposta
e
( ab + bc)² = [ (ab)² + 2 * ab * bc + (bc)² ] = a²b² + 2ab²c + b²c² **** resposta
Perguntas interessantes